Evaluation of the efficacy of regional anesthesia and intramuscular diclofenac in the management of postoperative pain: A comparative study - Ankita Raj; Priyanka Unnam; Richa Kumari; Shraddha Joshi; Bhushan Thoke; Shilpa Sunil Khanna (Wolters Kluwer Medknow Publications, 2021)
Aim: Managing postoperative pain following maxillofacial surgery is an important task. Our study aims to compare this with regional anesthesia or IM diclofenac. Materials and Methods: This study included 30 patients who underwent bi-jaw orthognathic surgery between April 2016 and January 2020. Two groups were formed. Group A was administered inferior alveolar nerve block at the surgical site bilaterally using 0.5% ropivacaine and Group B were administered 75 mg intramuscular diclofenac just before extubation. Tramadol HCl 2 mg/kg body wt is used as a rescue analgesic. The pain was evaluated periodically at 2nd, 4th, 6th, and 12 h postoperatively. Results: The mean Visual Analog Scale score was 2 in Group A and 5 in Group B. The mean duration of analgesia was 6 h 42 min, whereas in Group B, it was 8 h and 5 min. In 2 patients (13.3%) belonging to Group A and 3 patients (20%) belonging to Group B. There were no local complications in any group. Conclusion: It was observed that regional anesthesia in the form of intraoral nerve blocks was efficient than diclofenac (75 mg) administered intramuscularly for the management of immediate postoperative pain.